Integrasi Seleksi, Penempatan, Pengembangan Karir, dan Kesejahteraan dalam Perspektif Psikologi Organisasi - Ayi M. Sirojudin; Eti Kurniawati; Nurina Wulan Sabila (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to analyze the comprehensive relationship between selection, placement, career development, and employee well-being within the perspective of organizational psychology. Human resources (HR) are the central driver of organizational success, yet many institutions, including Islamic educational institutions, still face challenges in professional HR management. This research employs a library research method with a descriptive-comparative analysis approach, reviewing relevant scientific literature and empirical reports. The findings indicate that these four aspects form an integrated unit; effective selection based on person-organization fit provides quality candidates, appropriate placement optimizes potential, structured career development maintains motivation, and holistic well-being ensures loyalty and productivity. The study concludes that organizational success is heavily dependent on the synergy of these four components managed through an organizational psychology approach, rather than being treated as separate administrative functions.